Population parameters of two water scavenger beetles: Derallus angustus Sharp, 1882 and Enochrus vulgaris (Steinheil, 1869) (Coleoptera: Hydrophilidae) in permanent ponds: spatial distribution and microhabitat preference (Tropical Zoology, 2016)
The spatial distribution, temporal variation, and microhabitat preference of two populations of aquatic Coleoptera were analysed in permanent ponds located in the province of Corrientes, Argentina. Samples were collected every 15 days, between October 2010 and October 2011. The dispersion index and distribution models (Poisson Series, positive binomial and negative binomial) were used to evaluate the spatial distribution. For the evaluation of the microhabitat preference we used non-parametric Kruskal–Wallis test and then the Dunn test with the Bonferroni’s correction. In the test of the use of different microhabitats, we used a K proportion test and, when significant, a two proportion Z test was applied between pairs of microhabitats. The species analysed were the hydrophilids Derallus angustus Sharp and Enochrus vulgaris (Steinheil). The results indicate that the spatial distribution of individuals was mostly related to the homogeneity or heterogeneity of the ecosystem. However, when species were analysed individually, the spatial distribution and the use of microhabitat by each of them were different with respect to preference and behaviour. The macrophytes also play a role in the dynamics of these species, as they favour or limit the abundance by modifying the structure thereof.